If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 3x + 15 + -9x = 0 Reorder the terms: 15 + -7x + 3x + -9x = 0 Combine like terms: -7x + 3x = -4x 15 + -4x + -9x = 0 Combine like terms: -4x + -9x = -13x 15 + -13x = 0 Solving 15 + -13x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -13x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -13x = 0 + -15 -13x = 0 + -15 Combine like terms: 0 + -15 = -15 -13x = -15 Divide each side by '-13'. x = 1.153846154 Simplifying x = 1.153846154
| 6.9x-4+3x-1.8= | | 2y+1.5-4.3y+1.8y+1= | | (4x^2-9)(x^2-10)=0 | | 6/5y-2/5=-4y-1/3 | | -5(6n+1)=55 | | 11y/y | | 2x(3)=5x-4/3 | | 4x^3+4x^2=7x | | 25m^2-16/49 | | 7.48n+3.77=-3.22n+6.21 | | 8.08n+2.43=-3.13n+4.86 | | 8.08n+2.43=3.13n+4.90 | | 8.10n+2.45=-3.15n+4.85 | | 8.08n+2.43=3.13n+4.86 | | 7x-9=-38 | | (3x+1)2=5 | | log(6x+4)=1+log(x-5) | | -6r+250=-100+0.2(y-0.25y)+0.25y | | -6r+250=-100+0.2(y-0.25y) | | 8x-8=-9 | | r^2-12r-1=0 | | -[3z^2+4z-(2z^2-8z)]+[(9z^2-[5z-z^2])+5z^2]= | | -30=-6(3n-7) | | -30=6(3n-7) | | -8x+y-x+7y= | | .03x^2-9x+600=0 | | -(8-r)=-15 | | x^2+x+0.25=25 | | 3x+5x+10x=180 | | 3/4t-4=2 | | 6=-2+4(p+8) | | y/2-1=2 |